Multicentric Castleman's Disease in a Hepatitis C-Positive Intravenous Drug User: A Case Report. (11th April 2011) - Talukder, D. Y.; Delpachitra, S. N.
Abstract : Introduction . We report a rare presentation of Castleman's disease in a hepatitis C-positive patient and present a short review of treatments described in other similar case reports and studies. Case Presentation . A 46-year-old male with untreated hepatitis C and a 16-year history of intravenous drug use presented with pleuritic chest pain and bony pain in the knee, hip, and lower back, on a background of unexplained weight loss of 40 kilograms, fevers, night sweats, and repeated infections over the last two years. Examination discovered tender hepatomegaly, a warm right knee effusion, and painless lymphadenopathy. The patient was reactive to Epstein Barr virus and cytomegalovirus; however, HIV and HHV-8 viral testing was negative. Osteomyelitis of vertebrae T8–T11 and septic arthritis of the knee were found on investigation. A lymph node biopsy revealed histology suggestive of plasmacytic Castleman's disease. The patient is to commence rituximab treatment. Conclusion . Castleman's disease continues to present in novel ways, which may lead to difficulties in clinicopathologic diagnosis. A growing body of evidence suggests larger studies are required to determine the best treatment for multicentric Castleman's disease, particularly in patients with a concomitant disease, including hepatitis C.